1975
DOI: 10.1111/j.1365-2362.1975.tb00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Canalicular Bile Production in Man*

Abstract: Bile flow, erythritol clearance (measured after administration of 14-C-erythritol) and bile acid excretion were studied in 8 non-icteric patients operated upon for gallstone disease without biliary obstruction in whom a T-tube had been inserted. Bile flow increased from the 2nd (0.27 plus or minus SEM 0.01 ml/min) to the 7th (0.50 plus or minus SEM 0.05 ml/min) postoperative days and remained stable thereafter. Because the values obtained between the 7th and the 15th postoperative days (average: 0.46 plus or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Na+, K+-ATPase activity in LPMs from hypothyroid animals decreased by nearly 50% (5.4±1.6 /Amol P i/mg protein per h), although comparable re-INTRODUCTION Canalicular bile formation is a complex process which is dependent on the osmotic effects of bile salt excretion as well as a bile salt-independent mechanism (bile salt-independent flow [BSIF]) 1 (1,2). While canalicular excretion of bile salts results in a given fraction of bile per micromole of bile salts (3,4), BSIF consists of a relatively constant portion of basal flow that ranges from 20% of canalicular secretion in the dog (5), to over 50-60% in the rabbit (6) or rat (7)(8)(9), and 30% in man (10,11). BSIF may be induced by certain compounds such as phenobarbitol (7), and inhibited by other drugs, chemicals, or steroids (1).…”
mentioning
confidence: 99%
“…Na+, K+-ATPase activity in LPMs from hypothyroid animals decreased by nearly 50% (5.4±1.6 /Amol P i/mg protein per h), although comparable re-INTRODUCTION Canalicular bile formation is a complex process which is dependent on the osmotic effects of bile salt excretion as well as a bile salt-independent mechanism (bile salt-independent flow [BSIF]) 1 (1,2). While canalicular excretion of bile salts results in a given fraction of bile per micromole of bile salts (3,4), BSIF consists of a relatively constant portion of basal flow that ranges from 20% of canalicular secretion in the dog (5), to over 50-60% in the rabbit (6) or rat (7)(8)(9), and 30% in man (10,11). BSIF may be induced by certain compounds such as phenobarbitol (7), and inhibited by other drugs, chemicals, or steroids (1).…”
mentioning
confidence: 99%
“…This secretion creates an osmotic gradient which results in the passive transfer of fluid and electrolytes (21)(22)(23). It has also been recently reported that there is a bile acid-independent fraction of canalicular bile production both in animals (15,18,19) and man (20). THPP, 4-MU and AA-149 increased bile flow in rats by stimulating the canalicular bile formation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that canalicular bile production both in animals and man is due to bile acid-dependent and bile acid-independent fractions,and the latter is postulated to be mediated, at least partly, by an active sodium transport from hepatocytes to canaliculi (15,(18)(19)(20). Table 3 demonstrates the biliary excretion of bile acids and electrolytes after administration of THPP, 4-MU and AA-149 in rats.…”
Section: Bile Compositionmentioning
confidence: 99%
“…Bile acids are amphipathic and are capable of insertion into the lipid-water interphase as has been suggested for erythrocytes (29)(30)(31), thus resulting in altered membrane permeability to water, inorganic anions, and inert molecules such as inulin. Scanning electron microscopic studies from our laboratory demonstrated irregularities and outpouchings in the canalicular surface membranes Bile Flow (ml/24h) 300 FIGURE 8 Predicted differences in the diffusion permeability constant (K) during administration of7.0 ,umol/min taurocholic acid followed by 3.5 ,umol/min (solid lines) and 3.5 umol/min taurocholic acid followed by 7 of rats infused with bile acids, alterations which might occur through such a bile acid-canalicular membrane interaction and account for some of the differences in choleretic effect which we observed. In addition, an initial infusion of 7.0 gmol/min taurocholic acid might produce an increase in hepatic synthesis of phosphatydyl choline (24,25), thus resulting in an increase in the phospholipid:cholesterol ratio in canalicular membranes and enhanced membrane permeability, an effect not observed with dehydrocholic acid (14).…”
Section: Discussionmentioning
confidence: 99%
“…The osmotic gradient created by the concentration of bile acids in the canalicular lumen results in passive diffusion of water and electrolytes and produces bile flow. Recent investigations with inert markers of canalicular flow such as erythritol and mannitol suggest that this primary bile production in the rat (1,2), rabbit (3), rhesus monkey (4,5), and man (6,7) may not be entirely explained by the osmotic effects of the secreted bile acids. Sodium transport and the activity ofthe canalicular membrane-bound enzyme Na+, K+-ATPase have been postulated as possible determinants of this bile acidindependent canalicular secretion (3,8).…”
Section: Introductionmentioning
confidence: 99%